Genetic diversity for gliadin patterns of durum wheat landraces in the Northwest of Iran and Azerbaijan - Mohammad Zaefizadeh; Shahzad Jamaati-e-Somarin; Javid Ojaghi; Seyed Mehdi Seyedi; Roghayyeh Zabihi-e-Mahmoodabad; Mehran Ochi (Pesquisa Agropecuária Brasileira, 2010)
The objective of this study was to identify gliadin band patterns and the extent of genetic diversity in durum wheat genotypes from Northwestern Iran and the Republic of Azerbaijan. Gliadins from 46 landraces and four cultivars were evaluated through acid PAGE analyses. Sixty-six polymorphic bands and 81 patterns were identified. Twenty-four different motility bands and 22 patterns were found in the ω gliadin region with 14 polymorph bands and 20 patterns for α and γ gliadins, and 14 bands and 19 different patterns for β gliadins. The combination of these patterns generated 38 and 39 combinations for Gli-1 and Gli-2 loci, respectively. The genetic diversity index (H) was higher for α gliadins (0.924), followed by ω and γ gliadins (0.899 and 0.878, respectively), and for β gliadin patterns (0.866). Extensive polymorphism (H = 0.875) was observed in four gliadin pattern regions, with higher genetic diversity in the Iranian landraces than in the Azerbaijani ones. Each genotype had special identifying patterns in the gliadin acid PAGE analysis, and cluster analysis based on Jaccard's similarity coefficients formed six groups. Gliadin has a simple, repeatable and economic analysis, and can be used in genetic studies